ANCA-associated systemic vasculitides - Guillevin, Loic (Henry Stewart Talks, 2007)
Definitions and classification, PAN- versus ANCA-associated vasculitides, Epidemiology, Pathogenesis, Treatment, Optimization of conventional treatments, Assessment, New drugs and strategies, Relapses, Specific treatments for specific problems
Archived at 2018/10/25